Evaluation of the dental treatment needs of the institutionalized handicapped children in Tabriz - Asl Aminabadi; E Balaei (Isfahan University of Medical Sciences, 2007)
Introduction: The population of disabled children has been estimated more than 300 millions all over the world. Promotions of oral health and providing proper dental treatment for mental retarded people are two major challenges of health organization in every society. Assessment of treatment needs is the first steps in program planning for these children. The current descriptive-cross sectional study was conducted to evaluate the number of institutionalized mental retarded children and also their dental treatment needs in Tabriz institutions. Methods and Materials: 184 handicapped children (100 boys & 84 girls) aged 1 to 14 years old in private & governmental centers were examined from 2004 to 2005. An Observational-tactile technique was used and the results were recorded in a questioner. Data's were analyzed by SPSS 11 and Chisquare T-test. Results: The dental treatment needs were observed more frequently in the private centers (95.31%) in comparison to governmental centers (81.66%)(p < 0.05). The most prevalent dental treatment need was recorded in primary second molar (51.26%) and permanent first molar (67.53%).The most prevalent dental treatment need was restoration in primary dentition (62.93%) and permanent teeth (62.01%). Considering IQ, the highest value of dental treatment needs was seen in non trainable children (95.5%). The data were analyzed with T-test and Chi-square tests. Conclusion: Treatment needs value is higher in handicapped children. The prominent point is the severity of dental problems .Most of the dental treatments for these children could be done under general anesthesia in hospital so preventive plans are recommended strongly until the establishment of a specific center of dental care for these children. Key words: Mental retarded, Treatment needs, Institution, Handicap.